Melittin Inhibits Cell Growth, Alters the Cell Cycle Proﬁle and Induces Apoptosis in Hela Cells - Makkasau Plasay (Journal of Global Pharma Technology, 2017)
Conventional treatments for cancer are expensively and have serious side effect. Non-conventional natural treatments have gained acceptance because of minimal or no side effect, easy to find, but little scientific evidence exists. One of the anticancer candidates is melittin. Melittin is a venom protein isolated from bee venom. Presented here is the first reported effect of melittin on cell growth, cell cycle profile and apoptosis necrosis in HeLa cell line. The results show the melittin induce necrotic cell in dose dependent manner, but the IC25 shows the highest effect on apoptotic cell. All doses, IC10, IC25 and IC50 can inhibit G0/G1 on mitotic cell. Finally, the results may indicate the melittin potent to develop as anticancer drug.Keywords: Melittin, Cell growth, Cycle cell, Death.